Cervical cancer in Thailand: 2023 update - Mayuree Wongpratate; Sureewan Bumrungthai (Korean Society of Obstetrics and Gynecology, 2024)
Cervical cancer continues to pose a challenge to the health of Thai women, as the second most common cancer after breast cancer. Since high-risk human papillomavirus (HPV) types are the main cause for cervical cancer, cervical cancer screening and HPV vaccination are necessary to reduce the incidence of this disease. At present, the World Health Organization hopes to reduce the incidence of cervical cancer to 4 or less cases per 100,000 women-years using 90%-70%-90% intervention by 2030. The first intervention involves vaccinating 90% of women aged 15 years with the HPV vaccine. The second intervention involves screening 70% of women between the ages of 35 and 45 years using a high-performance screening test. The third intervention involves detecting cervical lesions in 90% of affected women to enable diagnosis and treatment. In this context, this study reviews trends in the incidence and mortality rates of cervical cancer in Thailand, in addition to providing an up-to-date overview of the causes and necessary risk factors for cervical cancer, as well as reporting on cervical screening and HPV vaccination rates and cervical cancer during the coronavirus disease 2019 (COVID-19) pandemic. This study may prove useful for the formulation of policy aimed at eliminating cervical cancer in Thailand, such as the implementation of a free HPV vaccine service and providing at-home kits for cervical screening through clinics and pharmacies. In addition, this review also highlights the need for further research on the effects of the COVID-19 pandemic on cervical cancer screening rates in Thailand.